Socio-Technical Innovation Bundles for Agri-Food Systems Transformation: Implications for Research and the One CGIAR Agenda - Sadoff, Claudia (2021)
Claudia Sadoff POLICY SEMINAR Socio-Technical Innovation Bundles for Agri-Food Systems Transformation: Implications for research and the One CGIAR agenda MAR 19, 2021 - 09:30 AM TO 11:00 AM EDT